Galveston on San Francisco Bay: Juneteenth in the Fillmore District, 1945–2016. Issue 2 (4th April 2019) - Blanck, Emily
Abstract: This article explores the history of Juneteenth—the commemoration of the emancipation of enslaved people in Texas—in San Francisco, California. In 1945, Wesley Johnson, a Texan migrant, introduced Juneteenth to San Francisco's Black community. The celebration sustained itself over seventy years, making it the longest continuous urban celebration of Juneteenth. Juneteenth remained relevant in San Francisco because it became intertwined with the history of African Americans in the Western Addition neighborhood. Most significantly, the holiday was a key expression of resilience as the city demolished the neighborhood in the 1960s, expelling much of the Black community. Surprisingly, later in the 1980s, the holiday became a key point of contact between the city and the Black community. This unlikely holiday continues in San Francisco to the present day.